Fig. 2 in High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015 ... - Virta, Miisa; Huitu, Otso; Heikkinen, Juha; Holmala, Katja; Jokelainen, Pikka (Zenodo, 2022)
Fig. 2. The estimated Eurasian lynx (Lynx lynx) population size and Toxocara cati prevalence (%, 95% confidence interval) in Finland, by year. ... : Published as part of Virta, Miisa, Huitu, Otso, Heikkinen, Juha, Holmala, Katja & Jokelainen, Pikka, 2022, High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015, pp. 205-210 in International Journal for Parasitology: Parasites and Wildlife 17 on page 208, DOI: 10.1016/j.ijppaw.2022.02.004, http://zenodo.org/record/13287925 ...